Elongation factor-2 kinase (eEF-2K) expression is associated with poor patient survival and promotes proliferation, invasion and tumor growth of lung cancer. (October 2018) - Bircan, Haci Ahmet; Gurbuz, Nilgun; Pataer, Apar; Caner, Ayse; Kahraman, Nermin; Bayraktar, Emine; Bayraktar, Recep; Erdogan, Mumin Alper; Kabil, Nashwa; Ozpolat, Bulent
Highlights: Eukaryotic elongation factor-2 Kinase (eEF-2K) is significantly upregulated in lung cancer cells. eEF-2K promotes tumor growth and invasion/metastasis ability of lung cancer cells. eEF-2K expression is associated with shorter overall survival in patients with lung cancer. High eEF-2K expression predicts short overall survival in lung cancer patients. eEF-2K may be a novel potential therapeutic target in lung cancer. Abstract: Objectives: Lung cancer is the leading cause of cancer related deaths in worldwide. Despite recent advances in treatment options, patient survival has not improved substantially due to lack of commonly expressed molecular targets and effective targeted therapeutics. Thus, better understanding of the biology of lung cancer and identification of novel therapeutic targets are urgently needed for development of highly effective molecularly targeted therapies. Materials and methods: Viability, proliferation and metastatic ability of lung cancer cells were evaluated using methylthiazoltetrazolium (MTT), colony formation and matrigel invasion assays, respectively. Western blotting, RT-PCR, and gene knockdown by siRNA transfections were carried out to investigate the effects of eEF-2K on lung cancer cells. Athymic Nu/Nu mice were treated with liposomal eEF-2KeEF-2K or control siRNA and tumor growth was evaluated in tumor xenograft models of lung cancer. Results and discussion: Here, we report that Eukaryotic Elongation Factor-2 kinase (eEF-2K), a member of an atypical alpha kinases family, is significantly upregulated in lung cancer cell lines and its expression is associated with shorter overall patient survival in lung cancer. Inhibition eEF-2K expression by siRNA or a chemical inhibitorsignificantly suppressed lung cancer cell proliferation, colony formation, survival, migration/invasion and tumorigenesis by inhibiting cyclin D1, Src and Mitogen-Activated Protein Kinases/Extracellular Signal-Regulated Kinase (MAPK/ERK) signaling. In vivo targeting of eEF-2K by systemically injected nanoliposomal eEF-2K siRNA resulted in a significant inhibition of lung cancer tumor xenografts in nude mice. Our results suggest, for the first time, that expression of eEF-2K is associated with poor patient prognosis and involved in regulation of critical pathways, including Src and MAPK/ERK and cyclin D1, promoting tumor growth and progression, and thus may be a novel potential therapeutic target in lung cancer.